Epithele odontioidea sp. nov. (Polyporales, Basidiomycota) from Eastern China - Li, Biao; Ma, Yushuo; Luo, Kaiyue; Zhang, Xin; Li, Zhenhao; Wu, Fang (Phytotaxa, 2025)
Wood-inhabiting fungi play a key role in ecosystem processes, especially in wood decomposition and the recycling of organic matter. A new wood-inhabiting fungus, Epithele odontioidea, collected from Eastern China, is illustrated and described based on morphological characteristics and phylogenetic analyses. The new species is characterized by resupinate, farinaceous basidiomata, white to grayish, odontioid hymenial surface due to hyphal pegs, monomitic hyphal system, generative hyphae with clamp connections, and ellipsoid to oblong-ellipsoid basidiospores measuring 13.2–18.2 × 6.8–8.7 µm. Phylogenetic analyses of the new species were conducted using internal transcribed spacer (ITS) and nuclear ribosomal large subunit (nLSU) sequences. The phylogenetic analysis indicated that the new species belongs to the genus Epithele and is grouped with the species E. efibulata. A description, illustrations, phylogenetic analysis results, and a comparison with the closely related species of the new species are provided.